Experimental study of passive seismic vibration isolation by trench-type periodic barrier. (1st February 2023) - Ramaswamy, Nagesh; Joshi, Bhagirath; Wang, Jiaji; Li, Xiaoliang; Menq, F.Y.; Shan, Xiaonan; Babu Nakshatrala, Kalyana; Stokoe, K.H.; Mo, Y.L.
Highlights: A comprehensive report of large-scale field tests for metamaterial-based barriers. T -Rex mobile shaker at UT Austin is used to generate excitation. Significant response reduction was observed for cases with metamaterial-based barriers. Various excitations result in similar results of frequency response function. Abstract: Seismic isolation systems protect structures and act as decoupling systems with the structure, which aims to uncouple the motion of the structure from incoming waves by reducing the kinetic energy of vibration transferred to structures. This research aims to study a non-invasive vibration isolation system using periodic barriers. A comprehensive field test program is completed to evaluate the wave isolation performance of empty trench and periodic barriers. The precast one-dimensional (1D) periodic barriers are arranged to form one long barrier and one short thick barrier to examine the influence of barrier length and the number of unit cells on the vibration isolation performance. The test program reported in this study is the P0 case (without periodic foundation), which serves as a reference group compared to previous test case P 1 (with periodic barrier and reinforced concrete foundation) and test case P 2 (with a combination of periodic barrier and periodic foundation). The triaxial ( T -Rex) shaker truck generates excitation in three axis and the wave form include sine wave, sweep frequency and seismic waves. Each geophone sensor position records the triaxial soil response. The responses of soil along the direction of wave transfer, the normalized responses, and the frequency response function (FRF) are all provided and discussed. Various excitation inputs are comparable. It is found that the excitation directions influence the periodic barrier's effectiveness because of the dominant waveform. When FRF is compared between benchmark case and test cases, the periodic barriers' screening effectiveness can be determined in the attenuation zones. These attenuation zones are expected to be the frequency band gaps of the periodic barrier. When the incoming wave frequency falls in this frequency band gap, the periodic barrier can isolate the vibration propagating towards the protected region.